The Impact of Legislation on Retail Food Prices in Serbia - Matović, Vladimir; Knezevic, Miroslav (Industrija, 2016)
The aim of the article was to find a link between the impact of legislation and retail prices of food products in Serbia. We have analyzed the whole domestic retail market of five main food groups, keeping in focus the largest retail companies and their portfolio of retail formats, and we have scanned the prices in 210 stores in 108 cities in Serbia.[1] The research was conducted before the introduction of the Regulation on limitation of margins on basic foodstuffs and also during its application, thus obtaining fully comparable data, having in mind that the same structures and product categories were observed. We got the expected results, meaning that the legislation has a direct impact not only on the amount of the sales price but also on its range within various retail formats, on compliance by format categories and regional compliance as well as overall price policy of trade companies and their way of negotiating with suppliers. The importance of this paper is reflected in the fact that a full study of the retail network of the largest trading companies has been conducted for the first time and their price formation policy of food products has been analyzed in conditions of their free formation as well as the conditions in which the methodology is prescribed by the state. Based on previous research, it has been proven that the prices of some food products were not formed on an economically justified level. [1] Retail prices were analyzed at facilities in different retail formats (hypermarket, supermarket, minimarket) in order to see the range of prices of identical products in the framework of one trading company but also within the same sales format in order to see a consistency in pricing policy, or the lack of it
Keywords: Food products; Prices; Retail